Trauma-associated acute kidney injury. Issue 6 (December 2019) - Perkins, Zane B.; Haines, Ryan W.; Prowle, John R.
Abstract : Purpose of review: A summary of recent research into the epidemiology, cause, management and outcomes of trauma-associated acute kidney injury (AKI). There is an increasing focus on subtypes of AKI to better target clinical management and future research. Recent findings: AKI associated with trauma occurs in 20–24% of patients admitted to ICU. On the basis of creatinine and/or urine output, AKI occurs in the first few days of traumatic illness. Although various associations have been identified, shock and high-volume blood transfusion are the most consistent risks for development of trauma-associated AKI. Short-term outcomes appear worse for patients with AKI, but extent of longer term kidney function recovery remains unknown. Recent research in the general critical care population is beginning to better inform AKI management; however, currently, preventive and supportive strategies remain the mainstay of AKI management after trauma. Summary: Well-designed, prospective research is required to better understand the phenotype, pathophysiology and recovery trajectory of trauma-associated AKI. Only then can potentially unique therapeutic targets be developed for this common subtype of AKI.